Corporate Citizenship: Missing The Point Or Missing The Boat? A Reply To Van Oosterhout - Crane, Andrew; Matten, Dirk (Academy of Management Review, 2005)
This article presents the authors' response to the comments of Hans van Oosterhout on their article, "Corporate Citizenship: Toward an Extended Theoretical Conceptualization."